Pemugaran Candi Padang Roco dan Candi Pulau Sawah di Kabupaten Dharmasraya (1995-2018) - Mifta Yulanda; Najmi Najmi (Galanggang Sejarah, 2023)
These temples were first discovered by a Dutch researcher named Verkerk Pistorius (1868) in the form of stacked bricks. After conducting excavations, the next restoration was carried out by a National Archaeological Research Center named Marsis Sutopo and the Compilation team from Batusangkar (BP3). The problem that occurred during the restoration was the lack of human resources around the temple. This study aims to determine the history of the restoration of Padang Roco Temple and Pulau Sawah Temple located in Jorong Sungai Langsat, Kenagarian Siguntur, Dharmasraya Regency. Based on the above, the cultural heritage area must be preserved so that it can be inherited for future generations. With data collection methods such as documents and interviews. The problems that occur when carrying out restoration are mainly the lack of human resources (HR) around, inadequate road access, and erratic weather. Looking at the problems that exist in the area of Padang Roco Temple and Pulau Sawah Temple, it is necessary to plan the preservation of cultural heritage areas which include protection, development and utilization.